'Wresting meaning from the market': a reassessment of Ludwig Lachmann's entrepreneur. Issue 3 (10th April 2013) - ENDRES, ANTHONY M.; HARPER, DAVID A.
Abstract: We undertake a close textual study of the entire corpus of Ludwig Lachmann's publications from 1936 to 1991 and demonstrate that his theory of entrepreneurial behaviour is sufficiently distinctive to warrant ranking alongside the theories of Schumpeter and Kirzner. Lachmann's entrepreneurs are creatively constructive change-agents who discover, exploit and create gaps in capital structures. Entrepreneurs select and interpret specific market and institutional phenomena using pre-existent rules and mental 'instruments', extract meaning about capital-forming opportunities, and generate all subsequent capital combinations. Lachmannian entrepreneurs are problem-solvers and communicate problem 'solutions' by dissolving and reforming capital combinations. We examine 20th-century Lachmannian research that builds on these foundations – research that emphasizes the institutional and material embeddedness of entrepreneurial behaviour and that appreciates the capacity of Lachmann's approach to explain entrepreneurial success, imitation and failure in a dynamic endogenous process. To underscore the distinctiveness of the Lachmannian entrepreneur, we compare it with Schumpeterian and Kirznerian approaches.